Anti-Inflammatory and Neuroprotective Effects of Constituents Isolated from Rhodiola rosea. (16th April 2013) - Lee, Yeonju; Jung, Jae-Chul; Jang, Soyong; Kim, Jieun; Ali, Zulfiqar; Khan, Ikhlas A.; Oh, Seikwan
Abstract : To determine the biological activity of Rhodiola rosea, the protein expression of iNOS and proinflammatory cytokines was measured after the activation of murine microglial BV2 cells by LPS under the exposure of constituents of Rhodiola rosea : crude extract, rosin, rosarin, and salidroside (each 1–50  μ g/mL). The LPS-induced expression of iNOS and cytokines in BV2 cells was suppressed by the constituents of Rhodiola rosea in a concentration-dependent manner. Also the expression of the proinflammatory factors iNOS, IL-1 β, and TNF- α in the kidney and prefrontal cortex of brain in mice was suppressed by the oral administration of Rhodiola rosea crude extract (500 mg/kg). To determine the neuroprotective effect of constituents of Rhodiola rosea, neuronal cells were activated by L-glutamate, and neurotoxicity was analyzed. The L-glutamate-induced neurotoxicity was suppressed by the treatment with rosin but not by rosarin. The level of phosphorylated MAPK, pJNK, and pp38 was increased by L-glutamate treatment but decreased by the treatment with rosin and salidroside. These results indicate that Rhodiola rosea may have therapeutic potential for the treatment of inflammation and neurodegenerative disease.